Coordination compounds cobalt bis(citrate)stannate - are results of searching new antiinfluenza drugs - M. V. Matyushkina; V. V. Godovan; I. I. Seyfullina; T. L. Grydina (LLC "Publisher OKI", 2014)
The pharmacological properties of new coordination compound - the biologically active substance - cobalt bis(citrate) stannate was studied. The result of researching are: the compound has antiviral activity against human influenza virus strains A/ Honghong/1/68 (H3N2), A/PR/8/34 (H1N1), and influenza virus H5N3 in tissue culture chorio-allantoic membranes (CAM) of chick embryos 11-12 daily and monolayer culture of MDCK cells used. Compound has a low toxicity (by intraperitoneal injection LD50 = 206,63 mg/kg; orally - LD50 = 1836,76), that gives perspective to further his preclinical studies as an antiviral agent.